The 1-Millisecond Challenge – Tactile Internet: From Concept to Standardization - Le, Duc Tran; Nguyen, Tri Gia; Tran, Thi Thu Thao (Journal of Telecommunications and the Digital Economy, 2020)
In recent years, Tactile Internet (TI) has become a familiar concept to humankind. It is expected to have the potential to create many new opportunities and applications that reshape our life and economy. However, the biggest challenge for recognizing the TI – the “1-millisecond challenge” remains unchanged, and it requires additional research efforts. In this paper, we will dissect what has been done and what needs to be done for the “TI ecosystem”. We will also investigate the TI concept from the perspective of the “network latency evolution”, as well as analyzing the architecture and the emerging technologies, which are needed to meet the strict requirements of the TI.